Effects of photobiomodulation therapy on performance in successive time-to-exhaustion cycling tests: a randomized double-blinded placebo-controlled trial - Lanferdini, Fábio Juner (2023)
The goal of this study was to investigate the effects of photobiomodulation therapy (PBMT) on performance, oxygen uptake (VO2) kinetics, and lower limb muscle oxygenation during three successive time-to-exhaustions (TTEs) in cyclists. This was a double-blind, randomized, crossover, placebo-controlled trial study. Sixteen cyclists (~23 years) with a cycling training volume of ~460 km/week volunteered for this study. In the first session, cyclists performed a maximal incremental test to determine maximal oxygen uptake and maximal power output (POMAX). In the following sessions, cyclists performed three consecutive TTEs at POMAX. Before each test, PBMT (135 J/thigh) or a placebo (PLA) was applied to both thighs. VO2 amplitude, O2 deficit, time delay, oxyhemoglobin (O2Hb), deoxyhemoglobin (HHb), and total hemoglobin (tHb) were measured during tests on the right vastus lateralis. The PBMT applied before three successive TTE increased performance of the first and second TTE (~10–12%) tests, speed of VO2 and HHb kinetics during the first test, and increased peripheral muscle oxygenation (increase in HHb and tHb) in the first and second exhaustion tests. However, the PBMT effects were attenuated in the third TTE, as performance and all the other outcomes were similar to the ones from the PLA intervention. In summary, PBMT application increased the first and second successive TTEs, speed of VO2, and muscle oxygenation.